Establishment of in vitro culture of rubber (Hevea brasiliensis) from field-derived explants: effective role of silver nanopeprintss in reducing contamination and browning - Moradpour, Mahdi; Abdul Aziz, Maheran; Abdullah, Siti Nor Akmar (Omics Publishing Group, 2016)
The development of in vitro methods to produce high quality clonal planting materials of c for replanting and new planting is highly essential. The establishment of in vitro cultures of challenging woody plant species like H. brasiliensis has frequently been hampered by persistent microbial contamination, phenolic production, phase change and low response to media. Therefore, the overall goal of this study was to establish an efficient in vitro propagation method for H. brasiliensis through solving those persistent problems. In determining the most suitable method of reducing explant contamination, different concentrations of sodium hypochlorite, mercuric chloride and nano silver (NS) at different immersion times were assessed on explants derived from three physiological leaf stages (bronze, light green and stable green leaf stages) of preculture and non-preculture treated plants. The highest percentage of survival (94.44%) was from explants derived from the light green leaf stage of preculture treated plants immersed in 10 ppm NS for 20 min. Different types of adsorbents which were silver nitrate, activated charcoal and NS were assessed in controlling browning of in vitro cultures of H. brasiliensis. NS at 4 ppm significantly produced the highest percentage of explant survival (87.03%) with a low percentage of browning (10%). In determining the most suitable medium for in vitro culture of H. brasiliensis explants, Murashige and Skoog (MS) medium, Woody Plant medium (WPM) and Enjalric and Carron (MB) medium in combination with 3%, 6% and 9% sucrose concentrations were assessed. After 16 weeks of culture, the highest percentage of shoot formation (80%) was on MB medium supplemented with 6% sucrose.